Carboxymethyl chitosan/clay nanocomposites and their copper complexes: Fabrication and property. (10th December 2015) - Huang, Yongcan; Huang, Jiancong; Cai, Jihai; Lin, Wensheng; Lin, Qixuan; Wu, Fangchengyuan; Luo, Jiwen
Highlights: A new type of environmentally friendly antifouling agent were prepared. The thermostability and antibacterial advantages of CMC, OMMT and Cu + was combined. CMC/OMMT–Cu nanocomposites showed high thermal stability. CMC/OMMT–Cu nanocomposites exhibited excellent antimicrobial activity. The lowest MIC of CMC/OMMT–Cu nanocomposite against E. coli was only 0.0003125%. Abstract: To obtain environmentally friendly antifouling agent, an effort was made to intercalate carboxymethyl chitosan into the interlayer of organic montmorillonite to prepare carboxymethyl chitosan/organic montmorillonite nanocomposites and their copper complexes. In comparison, carboxymethyl chitosan–copper complexes were also obtained. Their structures were characterized by X-ray diffaraction, transmittance electron microscopy and Fourier transform infrared, and their thermal behavior and antimicrobial activity were discussed. The results revealed that the interlayer distance of carboxymethyl chitosan/organic montmorillonite nanocomposites enlarged with the increasing mass ratio of carboxymethyl chitosan to organic montmorillonite, when the mass ratio was at 20:1, the layer spacing of carboxymethyl chitosan/organic montmorillonite nanocomposites reached the maximum of 3.68 nm. As compared to other samples, carboxymethyl chitosan/organic montmorillonite–copper nanocomposites showed much higher thermal stability and inhibitory activity against Escherichia coli, the lowest minimum inhibition concentration was only 0.0003125% (w/v). The study provides a new method to find novel antifouling agent.